Ecological strategies of Hyphantria cunea (Lepidoptera: Arctiidae) response to different larval densities - Zhao, XuDong; Geng, YiShu; Hu, TianYi; Xie, ChuXia; Xu, WenXuan; Zuo, Zhuang; Xue, MingYu; Hao, DeJun (Frontiers in Ecology and Evolution, 2023)
Population density is an essential factor affecting the life history traits of insects and their trade-off relationships, as increasing density intensifies intraspecific competition. It decreases the average resources available to individuals within a population, affecting their morphology, physiology, behavior, and fitness. The fall webworm, Hyphantria cunea (Drury) (Lepidoptera: Arctiidae), has been an invasive pest of forest trees, ornamental plants, and fruit trees in China for many years. The larvae have a typical aggregation habit before the fourth instar and keep spitting silk to gather the damaged leaves into silk webs. However, the fitness of H. cunea in response to population density remains unclear. In this study, the critical biological parameters, food utilization, and population parameters of H. cunea in response to different rearing densities were investigated. The results showed that under high population density, H. cunea larvae showed better performance, with faster development, higher survival rates, and shorter generation time, but pupal weight and female fecundity decreased as population density increased. In contrast, for larvae raised in low density, the developmental period was prolonged, and mortality was increased, while higher food utilization, greater body size, and female fecundity were observed. Both males and females had similar development strategies in response to the density, but females may be more resistant to crowding than males. In conclusion, H. cunea could adopt different ecological strategies against the stress of density. High population densities result in shorter generation cycles and higher survival rates. Conversely, the low-density generation period becomes longer but with greater fecundity. The results may help determine the possible outbreak mechanism and develop effective population monitoring and forecasting measures for H. cunea.